Cochrane Database of Systematic Reviews 2015
DOI: 10.1002/14651858.cd007572.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Anti-IL-12/23p40 antibodies for induction of remission in Crohn's disease

Abstract: Although we are uncertain about the efficacy of ustekinumab for induction of remission, moderate quality evidence suggests that ustekinumab may be effective for induction of clinical improvement in patients with moderate to severe CD. Due to small numbers of patients in dose subgroups the optimal dosage of ustekinumab is unclear. Briakinumab and ustekinumab appear to be safe. Due to sparse data we were unable to determine the risk of serious adverse events. Further studies are required to determine the efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…Remission rates were not significantly different between ustekinumab and placebo at week 6, but maintenance of remission was significantly higher in patients with an initial response to ustekinumab (41.7 vs. 27.4% placebo; p = 0.03) [24]. Compared to placebo, there was no significant increase in adverse events [20,25,26] except for injection site reactions noted in one study [17] and a higher number of severe infections in another study [24]. A Cochrane review [26] of both trials of ustekinumab in active CD [24,25] found the failure rate to achieve remission with ustekinumab not to be statistically different from placebo [relative risk (RR) 0.94, 95% CI 0.88-1.01] even when subgrouped by dose.…”
Section: Interleukin 12/23 Axismentioning
confidence: 99%
See 2 more Smart Citations
“…Remission rates were not significantly different between ustekinumab and placebo at week 6, but maintenance of remission was significantly higher in patients with an initial response to ustekinumab (41.7 vs. 27.4% placebo; p = 0.03) [24]. Compared to placebo, there was no significant increase in adverse events [20,25,26] except for injection site reactions noted in one study [17] and a higher number of severe infections in another study [24]. A Cochrane review [26] of both trials of ustekinumab in active CD [24,25] found the failure rate to achieve remission with ustekinumab not to be statistically different from placebo [relative risk (RR) 0.94, 95% CI 0.88-1.01] even when subgrouped by dose.…”
Section: Interleukin 12/23 Axismentioning
confidence: 99%
“…Compared to placebo, there was no significant increase in adverse events [20,25,26] except for injection site reactions noted in one study [17] and a higher number of severe infections in another study [24]. A Cochrane review [26] of both trials of ustekinumab in active CD [24,25] found the failure rate to achieve remission with ustekinumab not to be statistically different from placebo [relative risk (RR) 0.94, 95% CI 0.88-1.01] even when subgrouped by dose. Ustekinumab was, however, associated with a statistically lower rate of failure of response than placebo (RR 0.79, 95% CI 0.71-0.89), with a subgroup analysis showing a significant difference for the 4.5 mg/kg dose group [26].…”
Section: Interleukin 12/23 Axismentioning
confidence: 99%
See 1 more Smart Citation
“…These include the anti-TNF mAbs (infliximab, adalimumab, golimumab and certolizumab pegol) and two anti-integrin-blocking mAbs (natalizumab and vedolizumab). In contrast to the benefit evident in neutralising TNF, a contributing role for IL-17 in IBD is still uncertain, and IL-12/IL-23 are likely not the driver cytokines as there is only marginal efficacy from ustekinumab (anti-12/IL-23) in CD patients, and no benefit was evident in initial trials with briakinumab (anti-IL-12/IL-23 p40-neutralising mAbs) [54]. Indeed, brodalumab (anti-IL-17RA-neutralising mAb) caused worsening symptoms in CD [55].…”
Section: Inflammatory Cytokines In Psoriasis (And Psoriatic-type Arthmentioning
confidence: 99%
“…IL-23 sustains Th17 cell responses and gut inflammation 15 . The introduction of the anti-IL-12/23p40 antibody ustekinumab for the treatment of Crohn disease (CD), approved also for PsA and psoriasis, has contributed to the elucidation of a shared pathway between these pathologies based on the IL-23-driven process 16 .…”
mentioning
confidence: 99%